COCONUT YIELD IMPROVEMENT IN FARMERS' FIELDS THROUGH RESEARCH BASED FERTILIZATION MANAGEMENT IN THE PHILIPPINES - Severino S. Magat Ph.D. (International Coconut Community Journal, 1997)
For the past 20 years, the development of leaf analysis or foliar diagnosis ofcoconut, supported and confirmed by a network offertilizer experiments (onstation and on‑farm trials) demonstrated the significance of improving coconut yields in terms Of nuts and copra through balance nutrition or fertilization ofpalms. In the Philippines, emphasis on the correction of the widespread deficiencies in N, Cl, S and K had been achieved even in small‑scale farms with 142% average increase in nut yield and 179% increase in copra terms after 3‑4 years of application at moderate rates offertilizers. Research findings are discussed in relation to the coconut rehabilitation of mature stands and the utilization of coconut hybrids in the ‑ sustainable coconut development.